1994
DOI: 10.1346/ccmn.1994.0420401
|View full text |Cite
|
Sign up to set email alerts
|

The Diagenetic to Low-Grade Metamorphic Evolution of Matrix White Micas in the System Muscovite-Paragonite in a Mudrock from Central Wales, United Kingdom

Abstract: Abstract--Two orientations of white micas with subordinate chlorite have been observed in a fine-grained (50 ~, to 2 ~tm) matrix of a Silurian lower anchizonal mudrock from central Wales: one parallel to bedding and one parallel to cleavage that is approximately 30*-50 ~ to bedding. Bedding-parallel micas consist of small (50-200 ~ thick) deformed packets (IMd polytype) and larger (100 ~-2 t~m) strain-free grains (2M~ polytype). All strained micas and some strain-free grains have compositions varying from Mus~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…These authors observed transitions from illite-rich material with characteristics similar to those described above to mature micas and inferred that the transition represents a step (it is "episodic") triggered by tectonic activity. We conclude that the Basque-Cantabrian sequence is representative of the limits of passive burial metamorphism, at least insofar as transitions involving dioctahedral phyllosilicates are concerned, and that the deepest portions of the section overlap the conditions for tectonically-affected shale and slate sequences such as those described by Jiaug et al (1994) and Li et al (1994). For the BasqueCantabrian Basin, the burial temperature in the absence of tectonic stress could not cause any significant mineral changes, such as illite-phengite reaction, the 1Md --2M polytype transformation, or the change in crystal outline of SAED patterns, which have retained the turbostratic stacking order.…”
Section: Diagenetic Changessupporting
confidence: 58%
See 2 more Smart Citations
“…These authors observed transitions from illite-rich material with characteristics similar to those described above to mature micas and inferred that the transition represents a step (it is "episodic") triggered by tectonic activity. We conclude that the Basque-Cantabrian sequence is representative of the limits of passive burial metamorphism, at least insofar as transitions involving dioctahedral phyllosilicates are concerned, and that the deepest portions of the section overlap the conditions for tectonically-affected shale and slate sequences such as those described by Jiaug et al (1994) and Li et al (1994). For the BasqueCantabrian Basin, the burial temperature in the absence of tectonic stress could not cause any significant mineral changes, such as illite-phengite reaction, the 1Md --2M polytype transformation, or the change in crystal outline of SAED patterns, which have retained the turbostratic stacking order.…”
Section: Diagenetic Changessupporting
confidence: 58%
“…Prograde sequences have been studied from the Gasp6 Peninsula by Jiang et al (1994) and from Wales by Li et al (1994). They found that the lowest grades belong to the upper zone of diagenesis, extending through the epizone, and prograde changes were caused by tectonic stress.…”
Section: Diagenetic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed-layering of micas was not observed. Studying Silurian low-T anchizonal mudrocks from Wales by XRPD, TEM and AEM methods, Li et al (1994) demonstrated that the so called 6:4 ordered mixed-layer Pg/Ms originally described by Frey (1978) corresponds to an interlayer cation-disordered, homogeneous white mica of intermediate composition. This mineral formed from smectite by burial diagenesis.…”
Section: Dioctahedral Mixed K-na-micas and Paragonite In Diagenetic Tmentioning
confidence: 99%
“…Although the steps of reaction progress of these phyllosilicates and their precursor phases have been understood fairly well (Livi et al 1990;Li et al 1994;Livi et al1997), little work has been published dealing with the distinctive cause of their occurrences, i.e. which metaclastites do or do not contain paragonite and its precursor phases.…”
Section: Introductionmentioning
confidence: 99%